Clear micelle gel dosimeter with nanoclay. (August 2019) - Hayashi, K; Nemoto, M; Takanashi, T; Kang, Y; Togo, H; Kotoku, J; Kobayashi, T; Mihashi, M; Hayashi, S; Gotoh, H
Abstract: We built a clear micelle gel dosimeter with nanoclay. Jordan et al. reported that Laponite RD clay nanoparticles when added to radiochromic leucomalachite green micelle gels eliminate diffusion and increase the dose sensitivity by roughly ten folds. However, owing to the cloudiness of the sample, there was a problem in reading the optical computed tomography (CT). In this study, we constructed a nanoclay-added micelle gel dosimeter by changing the type of gelatin. As a result, in addition to yielding a clear gel and making the optical CT readable, diffusion and temporal stability were improved more than the gel without using nanoclay, and the dosimeter showed the same level of sensitivity and diffusion as the one based on Laponite-added micelle gel reported by Jordan et al.